Promoting early presentation of breast cancer in older women: sustained effect of an intervention to promote breast cancer awareness in routine clinical practice - Rachael H. Dodd; Alice S. Forster; Sarah Sellars; Julietta Patnick; Amanda J. Ramirez; Lindsay J. L. Forbes (BMC Health Services Research, 2017)
Abstract Background Older women have poorer survival from breast cancer, which may be at least partly due to poor breast cancer awareness leading to delayed presentation and more advanced stage at diagnosis. In a randomised trial, an intervention to promote early presentation of breast cancer in older women increased breast cancer awareness at 1 year compared with usual care (24 versus 4%). We examined its effectiveness in routine clinical practice. Methods We piloted the intervention delivered by practising health professionals to women aged about 70 in four breast screening services. We measured the effect on breast cancer awareness at 1 year compared with comparison services, where women did not receive the intervention. Results At 1 year, 25% of women in pilot services were breast cancer aware compared with 4% in comparison services (p = 0.001). The components of breast cancer awareness were knowledge of breast cancer non-lump symptoms (pilot: 63% vs comparison: 82% at 1 year; OR = 2.56, 95% CI 1.92-3.42), knowledge of age related risk (pilot: 8% vs comparison: 36% at 1 year; OR = 5.56, 95% CI 4.0-7.74) and reported breast checking (pilot: 70% vs comparison: 78% at 1 year; OR = 1.49, 95% CI 1.13-1.96). Conclusion The intervention may be as effective in routine clinical practice as in a randomised controlled trial. This intervention has the potential to reduce patient delay in the diagnosis of breast cancer in older women. Trial registration The PEP trial was registered with the International Standard Registered Clinical/soCial sTudy Number (ISRCTN) as a clinical trial ( ISRCTN31994827 ) on 3rd October 2007.